Study of the growth and survival of Heterotis niloticus fry (Cuvier, 1829) under rearing conditions in Kisangani (Tshopo, DRC) - Alexander-Armand, AMATCHO KALONDA; LIFINDIKI Joseph, BOTOMBATOMBA; Louison, OSAKO OMELONGA; Célestin, DANADU MIZANI; Roger, LINGOFO BOLAYA; Nathalie, NGALYA BENGE; Alidor, KANKONDA BUSANGA (Budapest International Research and Critics University, 2025)
The objective of this study was to evaluate the growth performance and survival of Heterotis niloticus fry based on local ingredients. A total of 120 fry with an initial weight of 6.9±5.2 g and an initial size of 4.5±3.1 cm in length were used for the experiment. After a seven-day acclimation period, these fry were randomly distributed in the 4 happas due to 30 fry per happa and two happens per feed. The experimental feeds were distributed manually to feed the fry until satiety, due to two feedings per day (8:30 a.m. and 4:30 p.m.). The feeding rate was given according to the body weight of the fish and readjusted after 2 weeks. For growth monitoring and survival of the fry, a sample of 40 fry was drawn from the happas due to 10 fry per happa every 6 weeks. The purpose of the operation was to measure the weight and total length of the fish. The experiment lasted 45 days. At the end of the study, the results obtained on growth and survival indicate that the average daily gain was 0.57 g/day for the fry fed with the T1 feed containing 36.5% animal protein and 0.46 g/day with the fry fed with the T2 feed containing 38% vegetable protein. The survival rate is 71.6 to 75% from one treatment to the next. The feed conversion ratio is 1.70 to 1.71 and the feed conversion ratio is 0.85 to 1.06 kg in the various treatments. The results as a whole show that pond rearing of H. niloticus can be considered for large-scale production and its extension should be encouraged.